The Effect of Giving Bit Juice with Prevention of Anemia in Pregnant Women in Trimester Iii at The Clinic of Dina Karya Medan in 2021 - Yuni Lestari; Willhemina Wahara; Julina Sembiring; Dalimawaty Kadir (Institute Of Computer Science (IOCS), 2022)
The World Health Organization (WHO) states that anemia is a serious global public health problem that especially affects women of childbearing age and pregnant women. The prevalence of anemia in women of childbearing age is 29.9%, in pregnant women 36.5%, in non-pregnant women 29.6%. Prevalence varies widely between countries and regions. The purpose of this study was to determine the effect of giving beetroot juice with the prevention of anemia in third trimester pregnant women. The research design used One Group Pretest-Posttest Design, namely one experimental research group by doing lactation massage. The population is 35 people. The sampling technique in this study used a purposive sample, with sampling using certain criteria, and the sample in this study amounted to 12 people. Data analysis is normality test, Paired Sample TTest test. The results showed that after the Shapiro Wilk test the results were obtained with a pretest with a value of .091 and a posttest with a value of .134, which means that the value of the results of Shapiro Wilk is normally distributed, that is > 0.05, and there is an effect of giving beetroot juice with the prevention of anemia in mothers. third trimester pregnant with pre_post statistical results obtained Sig. (2-tailed) is 0.000 < 0.05. So the conclusion is that there is an effect of increasing hemoglobin levels before and after being given beetroot juice to pregnant women in the third trimester. It is recommended for pregnant women in the third trimester to consume beetroot juice to prevent anemia.